1997
DOI: 10.1073/pnas.94.13.6676
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of novel mRNA motifs that bind special elongation factor SelB

Abstract: The special elongation factor SelB of Escherichia coli promotes selenocysteine incorporation into formate dehydrogenases. This is thought to be achieved through simultaneous binding to selenocysteyl-tRNA Sec and, in the case of formate dehydrogenase H, to an fdhF mRNA hairpin structure 3 adjacent to the UGA selenocysteine codon. By in vitro selection, novel RNA sequences (''aptamers''), which can interact tightly and specifically with SelB, were isolated from an RNA library. The library was comprised of mutage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…UGA-directed selenocysteine incorporation requires that this structure be located 11 nucleotides (nt) from the UGA codon (bold) (18). The U residue at position 17 is bulged (12,18). The pairing of boxes C 20 and G 27 is questionable (18) and is therefore designated by a dot instead of by a dash.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UGA-directed selenocysteine incorporation requires that this structure be located 11 nucleotides (nt) from the UGA codon (bold) (18). The U residue at position 17 is bulged (12,18). The pairing of boxes C 20 and G 27 is questionable (18) and is therefore designated by a dot instead of by a dash.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that this minihelix is the same 17-bp upper stem-loop structure that we showed is the minimal requirement for in vivo selenocysteine incorporation into a polypeptide (18). This minimal SECIS has a bulged nucleotide that has been shown to be crucial for selenocysteine incorporation (12,18).…”
Section: Discussionmentioning
confidence: 99%
“…Unbound RNAs were removed with selection buffer, and bound RNAs were eluted with denaturing buffer (30 mM Tris, pH 6.8͞20% glycerol͞2% SDS͞1 M DTT). Eluted RNA was amplified as described (24).…”
Section: Methodsmentioning
confidence: 99%
“…An RNA library with a complexity of 5 ϫ 10 14 different molecules was synthesised by in vitro T7-transcription from the PCRamplified synthetic DNA pool MF76.1: 5Ј-TCTAATACGAC-TCACTATAGGGCGCTAAGTCCTCGCTCA-N40-ACGC-GCGACTCGGATCCT-3Ј; primer MF39.1: 5Ј-TCTAATA CGACTCACTATAGGGCGCTAA GTCCTCGCTCA-3Ј (italic, T7-promotor; bold, BamHI restriction site); primer Mic20.1: 5Ј-GTAGGATCCGAGTCGCGCGT-3Ј (bold, BamHI restriction site) as described (21). CNBr-activated Sepharose was derivatized with synthetic peptides (CD18cyt, MF2G) or blocked with Tris⅐HCl (pH 8.0) alone according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%